2022
DOI: 10.1186/s42047-022-00111-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination method for the diagnosis of Tuberculous lymphadenitis in high burden settings

Abstract: Background India reports the highest number of extrapulmonary tuberculosis (EPTB) cases globally, most of which are lymph node TB (LNTB). In high tuberculosis (TB) burden countries rapid diagnosis is very important. Fine needle aspirate cytology (FNAC) diagnosis can be made with features of caseous necrosis with/without epithelioid granulomas. However, bacteriological confirmation is essential. This study was performed to evaluate the performance of the diagnostic tests available namely FNAC, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Studies showed that the Mtb bacilli load was very low in FNA samples [ 56 , 57 ] including the present study. Hence, FNA samples were excluded and bacilli load was enumerated only for PTB samples.…”
Section: Resultssupporting
confidence: 58%
“…Studies showed that the Mtb bacilli load was very low in FNA samples [ 56 , 57 ] including the present study. Hence, FNA samples were excluded and bacilli load was enumerated only for PTB samples.…”
Section: Resultssupporting
confidence: 58%
“…CTL is a health threat in Tunisia, and despite advances in molecular diagnostic tools, especially for patients without a history of TB, the diagnosis of CTL remains challenging ( 7 ). In the differential diagnosis of CTL, other granulomatous lymphadenitis, such as those caused by other bacterial diseases such as sarcoidosis, toxoplasmosis, tularemia, fungal disease, cat-scratch disease, and neoplasms, must be taken into consideration ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, imaging and evaluation of clinical symptoms are insufficient to conclusively diagnose CTL. Furthermore, the paucibacillary nature of CTL results in low sensitivity of bacteriological diagnostic tests ( 6 , 7 ). As a result, invasive sampling, such as fine needle aspiration and biopsies, is often required for a decisive diagnosis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“… 15 This is in contrast to a report on TB lymph node pathology in 100 immunocompetent patients, where 73% of cases showed caseous necrosis; as a result, the proportion for non-caseous necrosis is thought to be much higher in TOM. 16 However, many cases of TOM have also reported caseous changes in pathology. Furthermore, there is no evidence that non-caseous necrosis is more common in TB infections that occur in confined spaces such as the paranasal sinuses or nasal cavities.…”
Section: Discussionmentioning
confidence: 99%